Mal de Debarquement Syndrome - Saha, Kamala; Cha, Yoon-Hee (Seminars in Neurology, 2020)
Mal de debarquement syndrome (MdDS) is a disorder of persistent vertigo characterized by a feeling of oscillation such as rocking, bobbing, or swaying. It is triggered by passive motion, typically by exposure to water, air, or land transportation. This syndrome affects middle-aged individuals who are predominantly women. MdDS presents as a balance disorder that carries significant risk of morbidity due to both the direct effects of balance impairment and associated symptoms of fatigue, cognitive slowing, and visual motion intolerance. The Barany Society will be publishing criteria for diagnosing persistent MdDS. In addition, more insight has been gained into the pathophysiology of MdDS, with current hypotheses pointing to a cerebral and cerebellar basis. Treatments have expanded beyond medication trials, and now include the use of noninvasive brain stimulation and readaptation of the vestibulo-ocular reflex.
Keywords: mal de debarquement syndrome; persistent oscillating vertigo; disembarkment syndrome